(untitled) (International Journal of Nursing Education, 2020)
The damage extension of the SARS-CoV-2 virus, the cause of the coronavirus disease (COVID-19) outbreakthat started in December 2019, was completely unexpected. The virus infected more than 20.21 million andkilled more than 737,136 people as of 10th august 2020, leaving healthcare professionals under abnormalpressure. Although there are no estimates of how many are health care professionals infected, it may be15-18% of the healthcare professionals and suppose a correspondingly high death count. From emergencyphysicians and nurses to public health officers and psychologists, the exposure to distressing experiencespoints to a high chance of developing post-traumatic stress disorder, depression, and burnout syndrome. Inthe case of COVID-19, decisions upon scarce resources, frustration about patients’ outcomes, lengthenedworking hours, concerns regarding the family’s health, and widespread vicarious trauma are present andcostly for health care professionals. Coordinated reorganization of health and well managed social services isessential to assess and diagnose rapidly, treat patients effectively, and protect hospitals and health personnel.The policymakers were thinking that investing in the nursing sector and maintaining a professional nursingworkforce is an economic burden but now everyone is understood that they are especially for the wellbeingof our peoples and families. Hence it is necessary to support nursing professionals at the workplace andensuring the appropriate payout is a must along with appropriate timely training is required to ensure thequality service. Furthermore, they should be allowed to involve in policy formulation and decision makingall the time.